CASHLESS GOVERNMENT: A CORRUPTION PREVENTION STRATEGY IN GOVERNMENT AGENCIES - Paramita Nur Kurniati; Bernardus Yuliarto Nugroho (Asia Pacific Fraud Journal, 2020)
The phenomenon of corruption cases continues to increase from year to year, both from the number of cases that occur and the amount of state financial losses incurred. The criminal acts of corruption committed are also increasingly systematic and massive in all aspects of society's lives. To respond to this phenomenon, the Government, in this case the Ministry of Finance, issued a "breakthrough" in the system of government expenditure transactions, by issuing cashless government system with modern payment instruments. The cashless payment system is expected to close the potential gaps of corruption arising from conventional payment systems using physical money. Transactions carried out with non-cash payment systems can be traced in full and in detail, starting from who the user is, when and where the transaction is conducted, what is the purpose of using the transaction, and what is the nominal value. The use of cashless payment instruments is also expected to be able to fulfill the principles of (1) flexibility, (2) safety in transactions and fraud avoidance, (3) effectiveness, and (4) accountability while paying attention to the precautionary principles in the use of state budget. The cashless government system is expected to be a solution to the acceleration of government performance and public services within the framework of presenting clean, transparent and accountable governance. In the end, improving the working system of government organizations is expected to be able to encourage economic growth and provide benefits for improving the welfare of the community.